Impact of an Infrastructure Development Policy on Health, Poverty & Crime Actions in Indonesia (Case Study in Majalengka District) - Muhtar, Entang Adhy; Rusli, Budiman (International Journal of Criminology and Sociology, 2021)
With the construction of toll roads, the welfare of the people in the area has also changed. Toll road infrastructure plays a very important role in supporting the economy, social, culture, unity, and dynamics of community life. Majalengka Regency is one of the areas affected by the construction of the Cipali Toll Road (Cikampek-Palimanan). The results showed that in 2014, the life expectancy at birth in Majalengka Regency was only 68.66 years, and in 2019 it had reached 69.97 years. 85.43 percent of households live in their own houses, the remaining 14.57 percent of households live in houses that are not their own. When viewed at a glance, the percentage of own homeownership status in the 2018-2019 period, it can be seen that the percentage of the population who live in their own homes has increased by around 7 percent. The poor population in Majalengka Regency in total showed a downward trend during the 2015-2019 period (a condition in March). In 2015, the number of poor people was 167.50 thousand people or 14.19 percent of the total population of Majalengka Regency. In the 2019 period, the population who became victims of crime continued to experience a decline by 0.72 points to 0.88 percent compared to 2018 which reached 1.60.